2018
DOI: 10.1038/s41467-018-04010-4
|View full text |Cite
|
Sign up to set email alerts
|

The senescence-associated secretory phenotype is potentiated by feedforward regulatory mechanisms involving Zscan4 and TAK1

Abstract: The senescence-associated secretory phenotype (SASP) can be provoked by side effects of therapeutic agents, fueling advanced complications including cancer resistance. However, the intracellular signal network supporting initiation and development of the SASP driven by treatment-induced damage remains unclear. Here we report that the transcription factor Zscan4 is elevated for expression by an ATM-TRAF6-TAK1 axis during the acute DNA damage response and enables a long term SASP in human stromal cells. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 115 publications
(116 citation statements)
references
References 51 publications
3
112
1
Order By: Relevance
“…The biological effect of AREG is mainly mediated through its binding and activation of EGFR (also ErbB1), a widely expressed transmembrane RTK (Avraham & Yarden, ). By comparison of multiple cell lines and anticancer treatments, we showed that stromal cells are more ready to express AREG than cancer cells upon treatment by DDA agents that cause typical DNA lesions, instead of NDDA treatments that do not target DNA, a feature that is indeed shared by most of the SASP factors (Zhang et al, ). Intriguingly, AREG can be alternatively delivered via extracellular vesicles such as exosomes in the treatment‐naïve settings of multiple myeloma, non‐small‐cell lung cancer, and chronic myelogenous leukemia, each case activating the EGFR pathway in recipient cells without chemotherapy or SASP engagement in the TME (Corrado et al, ; Raimondo et al, ; Taverna et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effect of AREG is mainly mediated through its binding and activation of EGFR (also ErbB1), a widely expressed transmembrane RTK (Avraham & Yarden, ). By comparison of multiple cell lines and anticancer treatments, we showed that stromal cells are more ready to express AREG than cancer cells upon treatment by DDA agents that cause typical DNA lesions, instead of NDDA treatments that do not target DNA, a feature that is indeed shared by most of the SASP factors (Zhang et al, ). Intriguingly, AREG can be alternatively delivered via extracellular vesicles such as exosomes in the treatment‐naïve settings of multiple myeloma, non‐small‐cell lung cancer, and chronic myelogenous leukemia, each case activating the EGFR pathway in recipient cells without chemotherapy or SASP engagement in the TME (Corrado et al, ; Raimondo et al, ; Taverna et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to intrinsic resistance, which re‐exists in cancer cells before initiation of treatments, acquired resistance arises in the course of therapies and is frequently supported by the tumor‐adjacent stroma (Junttila & de Sauvage, ). For instance, cancer resistance can be driven by a treatment‐damaged TME, which is pathologically fueled by the SASP (Sun et al, , ; Zhang et al, ). Originally discovered as an essential biological feature of senescent cells, the SASP is now established as an important contributor in the development of multiple aging‐related complications, including atherosclerosis, osteoarthritis, physical frailty, and systemic inflammation (Childs et al, ; Demaria et al, ; Jeon et al, ; Zhu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As stromal cells represent the major non-cancerous mesenchymal components providing structural architecture within the tissue of most solid tumors, we chose to employ a primary normal human prostate stromal cell line, namely PSC27, to initiate the study. Composed of predominantly fibroblasts but with a minor percentage of non-fibroblast cell lineages including endothelial cells and smooth muscle cells, PSC27 develops a typical SASP after exposure to stressful insults such as cytotoxic chemotherapy or ionizing radiation [23][24][25] . We treated these cells with a pre-optimized sub-lethal dose of bleomycin (BLEO), resulting in enhanced senescence-associated βgalactosidase (SA-β-Gal) staining positivity, decreased BrdU incorporation, and elevated DNA damage foci several days afterwards ( Fig.…”
Section: Senescent Stromal Cells Generate An Increased Number Of Evsmentioning
confidence: 99%
“…Animals were sacrificed at end of the 8th week post tumor xenografting, with tumor volume measurement, tissue staining and histological examination performed as previously described 23 .…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Given the remarkable benefit of targeting KDM4 in the treatment-damaged TME, we subsequently evaluated longer time consequences by comparing the survival terms of animals subject to different treatment modalities in a time-extended manner. Development of a bulky disease was considered once the tumor burden was prominent (e.g., when the size exceeds 2000 mm 3 ), an approach reported previously 39,40 . Mice receiving MIT/ML324 co-treatment exhibited the most prolonged median survival duration, acquiring a minimally 50% longer survival than the group treated by MIT alone (Fig.…”
Section: Upregulated Kdm4a/b Expression Is Accompanied By Decreased Hmentioning
confidence: 99%